2014
DOI: 10.3945/an.113.004861
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Health Impact of Phosphorus in the Food Supply: Issues and Considerations

Abstract: The Western dietary pattern of intake common to many Americans is high in fat, refined carbohydrates, sodium, and phosphorus, all of which are associated with processed food consumption and higher risk of life-threatening chronic diseases. In this review, we focus on the available information on current phosphorus intake with this Western dietary pattern, and new knowledge of how the disruption of phosphorus homeostasis can occur when intake of phosphorus far exceeds nutrient needs and calcium intake is limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
109
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(115 citation statements)
references
References 44 publications
1
109
0
5
Order By: Relevance
“…13 In addition, the APD restitution properties (the dependence of APD of the preceding diastolic interval) are also important in determining the generation and maintenance of re-entry. 14,15 A steep APD restitution curve (small changes in diastolic interval yielding large changes in APD) is associated with the development of APD and CaT alternans (beat-to-beat variability). It will be more pronounced at rapid heart rates, where there will be a smaller diastolic interval between beats, resulting in greater alternans.…”
Section: Electrophysiology Resultsmentioning
confidence: 99%
“…13 In addition, the APD restitution properties (the dependence of APD of the preceding diastolic interval) are also important in determining the generation and maintenance of re-entry. 14,15 A steep APD restitution curve (small changes in diastolic interval yielding large changes in APD) is associated with the development of APD and CaT alternans (beat-to-beat variability). It will be more pronounced at rapid heart rates, where there will be a smaller diastolic interval between beats, resulting in greater alternans.…”
Section: Electrophysiology Resultsmentioning
confidence: 99%
“…Disruption of the calcium: phosphorus ratio because of excessive intake of inorganic phosphorus from food additives may affect endocrine regulation of the calcium balance. This could be detrimental for bone health (76). The negative association between the Western dietary pattern and bone health is in part accounted for by high net endogenous acid production.…”
Section: Healthy and Unhealthy Dietary Patternsmentioning
confidence: 99%
“…High adherence to the Western diet is associated with a high intake of fat, protein, refined carbohydrates, sodium, and phosphorus (76). High fat intake can directly interfere with intestinal calcium absorption.…”
Section: Healthy and Unhealthy Dietary Patternsmentioning
confidence: 99%
“…Pb can impair visual space cognition in centenarians, which might be an early symptom of dementia (Weisskopf et al 2007;Wright et al 2003), and in this study, it was found to have an adverse influence on centenarian age. Although P is considered an essential element, according to previous research, a high serum phosphate concentration is significantly associated with cardiovascular disease and increased mortality (Block et al 1998;Kestenbaum et al 2005;Slinin et al 2005), and an elevation in P can trigger the secretion of regulatory hormones, leading to tissue damage and the development of cardiovascular disease, renal impairment, and bone loss (Calvo et al 2014). Thus, excessive consumption of Pb and P should be avoided.…”
Section: Relationship Between Age and Element Concentrationsmentioning
confidence: 99%